UN chief calls for new era of social media integrity in bid to stem misinformation - UN News (UN News, 2023)
Countries must address the “grave global harm” caused by the proliferation of hate and lies online, UN Secretary-General António Guterres said on Monday, launching a key report designed to shore up information integrity on digital platforms.
Keywords: 2023-06 June